Imaging in movement disorders : imaging applications in non-parkinsonian and other movement disorders - Politis, Marios (International review of neurobiology, 2018)
Imaging in Movement Disorders: Imaging in Other Movement Disorders and Dementia, Volume 163 provides an up-to-date textbook on the use of imaging modalities across the spectrum of movement disorders and dementias. The book brings together lessons learned from neuroimaging tools in the content of movement disorders, including idiopathic and sporadic forms of Parkinson's disease, Huntington's disease, Atypical Parkinsonism, Dystonia, Essential Tremor, and more. Specific chapters cover Neuroimaging Applications in Dystonia, Neuroimaging Applications in Essential Tremor, Neuroimaging applications in Restless Leg Syndrome, Neuroimaging Application in Tourette's Syndrome and TIC Disorders, Neuroimaging Applications in Functional Movement Disorders, and Neuroimaging Applications in Cerebellar Disorders. Addition sections cover Molecular Imaging of Parkinson's Disease Cognitive Impairment, Structural MRI in Parkinson's Disease Cognitive Impairment, Functional MRI in Parkinson's Disease Cognitive Impairment, Molecular Imaging of Dementia with Lewy Bodies, Structural and Functional MRI of Dementia with Lewy Bodies, Transcranial Sonography in Movement Disorders, Imaging transplantation in Movement Disorders, Hybrid PET-MRI Applications in Movement Disorders, amongst other topics.